Pola Komunikasi Antarbudaya di Kelurahan Kampung Jawa Kecamatan Curup Tengah Kabupaten Rejang Lebong - Yuli Puspita Sari (Institut Agama Islam Negeri (IAIN) Curup, 2018)
This study explores or discusses the intercultural communication patterns found in the villages of the java in the sub district of Curup in the Central District of Rejang Lebong. There are five tribes in the village of Javanese village, namely the tribe of Lembak, Padang, Rejang, Java, Musi. Cultural differences that exist in the villages of the village of java do not lead to conflict and intercultural divisions, they respect each other from these disffences, but they see that their daily lives are closed and ignorant. The purpose of this study was to find out how the process of intercultural communication patterns in the villages of ward java communicate with different cultural backgrounds. The menhod used by the researcher is descriptive qualitative approach is used because the data needed by the author is only in the form of information and explanation from the informant. The data needed in this study was obtained through information from the village government, community leader, and the surrounding community. In data collection researchers used several techniques, namely observation, interviews, and documentation. The collected data is analyzed by data resuctio, data presentation (display), and verivikasi of data or drawing conclusions. From the results of the study it can be concluded that the intercultural communication patterns in the villages of the village of Java are obtained by the star’s communication pattern. Draving factors for intercultural communication are messages that are easy to understand, positive perception, and the same language.